The Impact of Digitalization and Higher Education in Improving Trade Performance in Southeast Asia with the Mediating Role of Private Sector Financing - Prasetyo Yuli Usaid (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the role of digitalization and higher education in trade performance in Southeast Asia by considering private sector financing as a mediating variable. The analysis is motivated by the growing importance of digital transformation and human capital quality as key determinants of trade performance in the context of global economic dynamics, as well as the role of financial systems in supporting real sector activities. The study adopts an explanatory quantitative approach using panel data from six Southeast Asian countries Indonesia, Malaysia, Thailand, Vietnam, the Philippines, and Singapore covering the period 2015–2024, sourced from the World Bank. Data analysis is conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with a bootstrapping procedure to examine both direct and indirect relationships among variables. The results indicate that digitalization plays a significant role in enhancing trade performance and is also significantly associated with private sector financing. Higher education is found to play a significant role in trade performance, but it does not show a significant relationship with private sector financing. Furthermore, private sector financing does not exhibit a significant role in trade performance and does not function as a mediating variable in the relationships between digitalization and trade performance, nor between higher education and trade performance. These findings suggest that the contributions of digitalization and higher education to trade performance in Southeast Asia tend to be direct, while the role of private sector financing as a transmission mechanism remains structurally constrained.